BALANCE OF HUMAN RIGHTS PRINCIPLES TOWARDS BLASPHEMY REGULATIONS IN LAW NUMBER 1 OF 2023 CONCERNING THE CRIMINAL CODE - Sayed Mursal; T Riza Zarzani (PT. Sinergi Legal Publisher, 2024)
Law Number 1 of 2023 concerning the Criminal Code (KUHP) brings significant changes to the Indonesian criminal law system, especially in terms of regulating the crime of blasphemy. This regulation aims to maintain public order and respect the religious values ​​​​adopted by the Indonesian people. However, this provision has sparked debate, especially regarding freedom of religion and expression. Some parties support this regulation to maintain social harmony, while others are concerned about the potential for abuse that can restrict individual freedom and hinder criticism of religious practices. This study uses a normative approach to analyze the conformity of this law with human rights principles, especially in the context of a multicultural society. The results of the analysis are expected to provide recommendations for the harmonization of fair and balanced regulations, so that there is no discrimination and restriction of freedom of expression in Indonesia.